1982
DOI: 10.1111/j.1365-2621.1982.tb11017.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Nonvolatile Minor Constituents Responsible for the Objectionable Taste of Defatted Soybean Flour

Abstract: A scheme was developed for the separation of the nonvolatile minor constituents from soy flour which are responsible for the astringent an bitter tastes. The scheme involved solvent extraction, freeze drying, and fractional crystallization. Two fractions, collected by semipreparative HPLC, had the characteristic bitter and astringent tastes. Further fractionation by reverse phase HPLC produced three pure compounds which were identified by UV, NMR spectrometry and elemental analysis, as daidzein, glycitein 7$-O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
1
1

Year Published

1987
1987
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 8 publications
1
28
1
1
Order By: Relevance
“…The threshold value of the soyasapogenol A aglycone was higher than those of saponin A group, and a similar relationship was found for other saponins and their aglycones.. The threshold value of daidzin was 10-5 -10- 6 M, and that of daidzein, its aglycone, was 10-6 M. The value of genistin (10 -5 M) was lower than that of genistein (l0-4 M). This result contrasts with those found for the saponins.…”
Section: Threshold Value {Mm)mentioning
confidence: 71%
“…The threshold value of the soyasapogenol A aglycone was higher than those of saponin A group, and a similar relationship was found for other saponins and their aglycones.. The threshold value of daidzin was 10-5 -10- 6 M, and that of daidzein, its aglycone, was 10-6 M. The value of genistin (10 -5 M) was lower than that of genistein (l0-4 M). This result contrasts with those found for the saponins.…”
Section: Threshold Value {Mm)mentioning
confidence: 71%
“…From a sensory perspective, a higher amount of isoflavone may adversely affect the flavor of SPI/SG9:1, SPI/SG6:4 and SPI/SG3:7. Huang, Hsieh, and Chang (1981) and Kudou et al (1991) reported that isoflavones contribute to the undesirable bitterness and astringency associated with soy foods.…”
Section: Enrichment Of Isoflavone Aglycones In Fermented Soymilk Compmentioning
confidence: 97%
“…The limitation of genistein bioavailability after oral administration is generally due to its poor water solubility (74). Genistein also has a bitter taste (75), and formulations to overcome both the limitation of bioavailability and acceptable taste are necessary. Extensive metabolism of genistein in the intestine and postabsorption has been documented both in humans and experimental animals.…”
Section: Bioavailabilitymentioning
confidence: 99%